Decadal predictability of North Atlantic blocking and the NAO - P. Athanasiadis, A. Bellucci (Zenodo, 2019)
Documenting unprecedented decadal predictability for midlatitude atmospheric circulation anomalies over the North Atlantic (NAO and blocking) evaluated with the CESM-DPLE simulations by NCAR. Work in progress to include all DCPP decadal hindcast simulations into a multi-model study.